An Investigation of ESL learners’ Affective Attributes Toward Online Reading - Kangxing, Dong (UMP, 2022)
The Covid-19 pandemic has remarkably expedited the growth of digital culture and made online reading an indispensable element of students’ academic journey. Students need to read online to learn new lesson contents and complete assignments. As educators and teachers, it is important to understand clearly our students’ affective attributes toward online reading as these affective attributes play a significant role in students’ reading process. The present study examined three affective attributes toward online reading among Malaysian ESL learners at the tertiary level, i.e., self-efficacy, motivation and anxiety. The data were collected by using the questionnaire Survey of Online Reading Affective Attributes. This questionnaire was adapted by the researcher from previous questionnaire studies to measure students’ affective attributes toward online reading for academic and study-related purposes. This questionnaire survey was administered to 130 ESL learners at the tertiary level. The results revealed the following findings: (a) tertiary ESL learners had relatively positive affective attributes toward online reading, (b) no significant differences were found in terms of self-efficacy, motivation and anxiety between male and female students, (c) self-efficacy, motivation and anxiety in the online reading context were significantly correlated with one another. Some recommendations for future studies were also provided.